2008
DOI: 10.1017/s1368980007001504
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cardio-metabolic risk by BMI and waist circumference among a population of Guatemalan adults

Abstract: Background: BMI and waist circumference (WC) are used to screen for cardiometabolic risk; however it is unclear how well these indices perform in populations subject to childhood stunting. Objectives: To evaluate BMI and WC as indicators of cardio-metabolic risk and to determine optimal cut-off points among 1325 Guatemalan adults (44 % stunted: #150 cm women; #162 cm men). Methods: Cardio-metabolic risk factors were systolic/diastolic blood pressure $130/$85 mmHg, glucose $5?5 mmol/l, TAG $1?7 mmol/l, ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Al-Lawati et al in 2008 [ 24 ], reported the optimum BMI cut-off for the Omani Arab population as 23.2 kg/m 2 and 26.8 kg/m 2 for men and women older than 20 years old, respectively. In another study [ 25 ] evaluating BMI based on metabolic risk factors conducted in Guatemala, as a developing country, they documented BMI cut-offs similar to our study as 24.7–26.1 kg/m 2 for men and 26.5–27.6 kg/m 2 for women.…”
Section: Discussionsupporting
confidence: 85%
“…Al-Lawati et al in 2008 [ 24 ], reported the optimum BMI cut-off for the Omani Arab population as 23.2 kg/m 2 and 26.8 kg/m 2 for men and women older than 20 years old, respectively. In another study [ 25 ] evaluating BMI based on metabolic risk factors conducted in Guatemala, as a developing country, they documented BMI cut-offs similar to our study as 24.7–26.1 kg/m 2 for men and 26.5–27.6 kg/m 2 for women.…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted in Colombian subjects with no previous CVD history, reported that the criteria for waist circumference proposed by the International Diabetes Federation (90 cm: men, 80 cm: women) is more useful for identifying subjects with MetS than that proposed by the Adult Treatment Panel III (102 cm: men, 88 cm: women) [ 22 ]. In addition, several studies [ 109 , 110 ] carried out in developing countries have reported lower waist circumference cutoff points for cardiovascular risk than those reported in developed countries. In healthy young Colombian men, a waist circumference of 88 cm identified subjects with cardiovascular risk with a sensitivity of 83.7% and a specificity of 84.8% [ 111 ].…”
Section: Abdominal Obesity Insulin Resistance and Low Degree Inflammmentioning
confidence: 97%
“…[37][38][39][40][41][42][43][44] Few studies have investigated the use of cut-off points in Western population, such as, in Spanish population the optimal BMI cut-off for predicting BF% were above 26 kg/m 2 in men and 24 kg/m 2 in women were associated with to 25% and 35% of BF%, respectively. 31,45,46 Already, in Mexican population showed the BMI cut-off to predict hypertension varied from 25.2 to 26.6 kg/m 2 in both men and women. 45 In accordance, our study has resulted in similar cut-off values, where showed 28 kg/m 2 in men and 26 kg/m 2 in women that corresponded to 25% and 35% of BF%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In disagreement other studies, in Guatemalan population the optimal cut-off points for BMI were slightly higher among women (27.6 kg/m 2 ) than men (25.9 kg/m 2 ) with no meaningful differences by stature. 46 The abdominal obesity is highly correlated to insulin resistance and was also associated with an increased risk of myocardial infarction, stroke and premature death, whereas these diseases were not associated with measures of generalized obesity such as BMI. 47 In the 2001 NCEP ATP III guidelines, abdominal obesity was defined as a WC ≥102 cm in males and ≥88 cm in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation